Analysis Of Concurrent Delays on Multiple Critical Paths - جراد فايز (Latakia University Journal -Engineering Sciences Series, 2022)
Delay analysis is an important problem in construction management. The analysis is difficult when there are concurrent delays. Sorting concurrent delays is a basic step during analysis. A suitable technique must be used to apportion compensation or damages in an equitable manner. In this research, the problem of concurrent delays is discussed in detail and the difference between concurrent delays on delayed critical paths and primary critical paths is also discussed. Consequently, concurrent delays are considered on primary critical paths only. Many problems related to multiple primary critical paths with or without concurrent delays are introduced in this research. The author proposes a new method called the percentage method, which overcomes the presented problems. The new method can be used in the following cases: one primary critical path or multiple primary critical paths with or without concurrent delays.